Correlation between spiritual health, anxiety, and sleep quality among cancer patients - Zahra Khalili; Edris Habibi; Naser Kamyari; Shahin Tohidi; Vahid Yousofvand (Elsevier, 2024)
Background: Receiving a cancer diagnosis constitutes a profoundly distressing and disconcerting experience for patients, often resulting in a loss of existential meaning. Consequently, individuals grappling with such diagnoses frequently manifest symptoms of anxiety and sleep disorders, impeding their adaptation to the challenges posed by the illness. In light of this, this research paper explores the correlation between spiritual health, anxiety, and sleep quality among cancer patients. Methods: The study was conducted in Hamadan, Iran's Shahid Beheshti Hospital's oncology department, over a one-year period. A total of 222 cancer patients were selected through convenience sampling. Data were collected using questionnaires on demographic information, Islamic spiritual health, Beck anxiety, and Pittsburgh sleep quality. Results: The results showed a negative correlation between spiritual health and anxiety (r = -0.232, p < 0.05), indicating that patients with lower spiritual health had higher anxiety levels. Similarly, there was a negative correlation between anxiety and sleep quality (r = -0.146, p < 0.05), suggesting that higher anxiety was associated with poorer sleep quality. However, there was no significant correlation between spiritual health and sleep quality (r = 0.032, p > 0.05). Limitations: The limitations of the study include the use of self-report questionnaires and the potential impact of COVID-induced anxiety. Conclusion: The study concludes that healthcare providers should assess and address the needs of cancer patients, including providing spiritual care, to reduce anxiety and improve sleep quality. Overall, the findings highlight the importance of incorporating spiritual care into cancer patients' treatment plans to enhance their well-being.